1997
DOI: 10.1128/jvi.71.3.1814-1820.1997
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of the coronavirus infectious bronchitis virus 1a polyprotein: identification of a 10-kilodalton polypeptide and determination of its cleavage sites

Abstract: Proteolytic processing of the polyprotein encoded by mRNA 1 is an essential step in coronavirus RNA replication and gene expression. We have previously reported that an open reading frame (ORF) 1a-specific proteinase of the picornavirus 3C proteinase group is involved in processing of the coronavirus infectious bronchitis virus (IBV) 1a/1b polyprotein, leading to the formation of a mature viral protein of 100 kDa. We report here the identification of a novel 10-kDa polypeptide and the involvement of the 3C-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 23 publications
3
90
0
Order By: Relevance
“…NSP5 was similar by 52%, 44%, and 92% at the nucleotide sequence level and by 39%, 44%, and 93% at the amino acids level to HCoV-229E, BCoV, and IBV, respectively. This region was believed to play a critical role for ORF1b processing since the deletion of NSP5 in IBV resulted in the unprocessing of 1b protein (Liu et al, 1997). NSP3, NSP4 and NSP6 were predicted to carry a hydrophobic transmembrane domain which may play an important role in the transcription/replication process as recently discussed for other coronaviruses (Sawicki et al, 2007).…”
Section: Gene 1-viral Replicasementioning
confidence: 88%
“…NSP5 was similar by 52%, 44%, and 92% at the nucleotide sequence level and by 39%, 44%, and 93% at the amino acids level to HCoV-229E, BCoV, and IBV, respectively. This region was believed to play a critical role for ORF1b processing since the deletion of NSP5 in IBV resulted in the unprocessing of 1b protein (Liu et al, 1997). NSP3, NSP4 and NSP6 were predicted to carry a hydrophobic transmembrane domain which may play an important role in the transcription/replication process as recently discussed for other coronaviruses (Sawicki et al, 2007).…”
Section: Gene 1-viral Replicasementioning
confidence: 88%
“…The 5 twothird region of mRNA1 comprises two large ORFs, 1a and 1b, and encodes two polyproteins. The two polyproteins are cleaved proteolytically by two virus-encoded proteinases, the papain-like and 3C-like proteinases, into 15 functional proteins (Nsp2-Nsp16) (Liu et al, 1995(Liu et al, , 1997Ng and Liu, 1998Xu et al, 2001). Compared to other coronaviruses, Nsp1 is absent in IBV but Nsp2 is considerably larger (Lim and Liu, 1998a,b;Lim et al, 2000;Liu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with the previous researches on the prediction and identification of 3CLpro cleavage sites, the scanning condition IV showed its advantages. For example, the two nonexistent putative cleavage sites predicted within nsp6 of IBV (Gorbalenya et al, 1989;Liu et al, 1997;Ng and Liu, 1998) were avoided in our prediction method (data not shown). Notably, the noncanonical cleavage site at the end of MHV nsp7 identified by Deming et al could be predicted using scanning condition IV.…”
Section: Discussionmentioning
confidence: 99%
“…Some cleavage sites have been identified and confirmed by previous studies, including three cleavage sites of PLpros of human coronavirus 229E (HCoV 229E), mouse hepatitis virus (MHV), SARS-CoV, MERS-CoV and infectious bronchitis virus (IBV), whose cleavages release the first 3 non-structural proteins (Bonilla et al, 1995;Kilianski et al, 2013;Lim and Liu, 1998;Ziebuhr et al, 2007). The canonical cleavage sites of 3CLpros, the sites between the recognized nsps, have also been characterized, including all sites of MHV, IBV, SARS-CoV and a fraction of sites of HCoV 229E which release the non-structural proteins from nsp4 to nsp16 (Deming et al, 2007;Grotzinger et al, 1996;Liu et al, 1994Liu et al, , 1997Lu et al, 1995). For 3CLpro of MERS-CoV, two cleavage sites releasing nsp4 to nsp6 have been identified (Kilianski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation